Two variables affecting the economic value added (EVA) - Honková, Irena (Masarykova univerzita, 2017)
Economic value added EVA is one of the most important indicators of financial analysis, however, it has not been being used widely in practice yet. A possible reason is its calculation that is more complicated than for conventional one, e.g. ratios. This complexity primarily involves calculating the average weighted cost of capital (WACC) and unequal approach to the calculation of net operating profit after tax (NOPAT), the WACC and NOPAT are initial variables for the calculation of EVA. The aim of this paper is to summarize the basic approaches to calculating WACC, particularly the cost of equity and to calculate NOPAT and finally to simplify the calculation of EVA with mathematical analogy modifications. Mathematical adjustment has proved that economic value added is essentially a net profit weighted by the debt proportion in the overall capital structure. This post is to submit a simplification of the indicator of economic value added in an effort to extend its application in practice.
Dvě proměnné ovlivňující ukazatel Ekonomické přidané hodnoty (EVA) Dvě proměnné ovlivňující ukazatel Ekonomické přidané hodnoty (EVA) Dvě proměnné ovlivňující ekonomickou přidanou hodnotu (EVA)
Keywords: Economic value added; EVA; Average weighted cost of capital; WACC; Net operating profit after tax; NOPAT.; Ekonomická přidaná hodnota; EVA; Průměrné vážené náklady na kapitál; WACC; Čistý provozní zisk po zdanění; NOPAT.